CALCULATION OF RADIONUCLIDE CONTENT OF NUCLEAR MATERIALS USING ORIGEN2.1 COMPUTER CODE - Ihda Husnayani (Badan Tenaga Nuklir Nasional, 2015)
Nuclear materials contain a number of radionuclides produced from radioactive decay process. The composition of these radionuclides which are accumulated in-side the nuclear materials changes over the time. The calculation of radionuclide composition inside nuclear materials is very important especially in the aspect of nuclear reactor safety evaluation, nu-clear fuel behavior evaluation, and radioactive waste management. One method to calculate radionu-clide content of nuclear materials is by using ORIGEN2.1 computer code. Beside radionuclide com-position, this code can also calculate some characteristics related to decay process such as total radio-activity, decay heat, and neutron flux. This paper is a literature study about ORIGEN2.1 computer code. A brief description of ORIGEN2.1 and its use for calculating radionuclide content of nuclear materials are presented. Radionuclide content produced from californium-252 decay was chosen as a simple case solved by ORIGEN2.1. Californium-252 was simulated to undergo decay for 10 years. The variables which are calculated by ORIGEN2.1 in this case are radionuclide composition, total radioactivity, total alpha radioactivity, and neutron flux. From the results of this simulation, it is shown that small amount of californium-252 produces high neutron intensity so that it can be used as a reliable neutron source for many applications.